Reconceptualizing Speaking Self-Efficacy and Learning Motivation in Arabic Higher Education: Evidence from Indonesian Islamic Universities - Nida Ul Khasanah; Budi Sanjaya; Zakiyatunnisa Al Mubarokah (Universitas Islam Negeri Palangka Raya Raya, 2026)
Speaking competence occupies a central position in Arabic language education, yet students in Arabic Language Education programs often encounter psychological challenges that affect their confidence and motivation to develop oral communication skills. While previous studies have discussed speaking proficiency, anxiety, and motivation in foreign language learning, the relationship between speaking self-efficacy and learning motivation in the context of Arabic higher education, particularly in Indonesian Islamic universities, remains insufficiently explored. Therefore, this study investigates the correlation between speaking self-efficacy and learning motivation among students of the Arabic Language Education Study Program. A quantitative correlational design was employed, involving all 62 third-semester students at UIN Sulthan Thaha Saifuddin Jambi through total sampling. Data were collected using a validated Likert-scale questionnaire and analyzed using descriptive statistics and Pearson’s Product-Moment correlation. The results showed that students’ speaking self-efficacy and learning motivation were generally at moderate to high levels. The magnitude dimension emerged as the strongest component of self-efficacy, while persistence in effort was the dominant indicator of motivation. The correlation analysis revealed a strong and significant positive relationship between speaking self-efficacy and learning motivation (r = 0.893; p < 0.001). These findings suggest that strengthening students’ speaking self-efficacy through successful learning experiences, constructive feedback, and emotion regulation may substantially enhance their motivation to learn Arabic speaking skills.